Speciation by hybridization in Heliconius butterflies (2006)
Speciation is generally regarded to result from the splitting of a single lineage. An alternative is hybrid speciation, considered to be extremely rare, in which two distinct lineages contribute genes to a daughter species. Here we show that a hybrid trait in an animal species can directly cause reproductive isolation. The butterfly species Heliconius heurippa is known to have an intermediate morphology and a hybrid genome1, and we have recreated its intermediate wing colour and pattern through laboratory crosses between H. melpomene, H. cydno and their F1 hybrids. We then used mate preference experiments to show that the phenotype of H. heurippa reproductively isolates it from both parental species. There is strong assortative mating between all three species, and in H. heurippa the wing pattern and colour elements derived from H. melpomene and H. cydno are both critical for mate recognition by males.